Worry about victimization, crime information processing, and social categorization biases - Gouseti, Ioanna (Legal and criminological psychology, 2018)
Purpose. This study explores associations between worry about victimization, crime information processing, and social categorization biases. Its results speak to the public communication of the crime-risk. Methods. The study tests hypotheses that draw on the construal-level theory of psychological distance and the uncertainty-identity theory. Through an online experiment that was conducted in 2015 on Amazon Mechanical Turk (N = 312), three experimental groups were exposed to different modes of crime information processing and were then asked about their worry about victimization and attitudes to social categorization. Results. The results suggest that passive engagement with information about real crimes, that is only reading about them, is more likely to decrease levels of worry about victimization compared to engaging with such information actively, that is by thinking about causes or consequences of crime. It is also found that worry about victimization is significantly related to social categorization biases, namely in-group identification, outgroup derogation, and racist attitudes. Conclusions. The mode of crime information processing (active vs. passive) appears to be a strong ‘predictor’ of worry about victimization. In turn, worry about victimization is related to social categorization biases that damage collective well-being. These findings can feed into evidence-based strategies for the public communication of crime that keep people informed but free from fear.